Ending the Detention of Children: Developing an Alternative Approach to Family Return - Heaven Crawley (Swansea University, 2010)
The Conservative-Liberal Democrat Government Coalition Agreement of 10th May 2010 included a commitment to “end the detention of children for immigration purposes”. On 25th May it was announced that a review of existing practice in the UK and elsewhere would be undertaken in order to identify how this commitment would be achieved. The terms of reference for the review were published on the UK Border Agency (UKBA) website on 11th June1 and debated in the House of Commons on 17th June. This paper on alternatives to detention has been produced to inform the review process. It draws upon an existing body of research in the UK and internationally to develop an alternative approach to family returns which does not rely upon detention to secure the forced removal of families but rather increases the willingness and ability of those whose claims have been unsuccessful to return to their countries of origin. This approach takes into account the rights and needs of children and their parents, whilst recognising that those who are not entitled to remain in the UK will be required to leave the country at the end of the asylum process. The paper focuses on alternatives to detention for children in asylum seeking families for whom there may be particular barriers to return.